Participatory Action Research Dalam Pengembangan Kewirausahaan Digital Di Pesantren Perkotaan - Ahmad Syafii Rahman; Cipto Sembodo; Retno Kurnianingsih; Faishol Razak; Muhammad Nur Kholis Al Amin (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2021)
The Al-Muayyad Islamic boarding school as one of the oldest Islamic schools in the urban area of ​​Surakarta is encouraged to become a driving force for the entrepreneurial based on the pesantren-based digital creative economy sector through the participatory action research (PAR) approach. The PAR approach was chosen because it has the characteristics of the joint process between the research subject and the researcher as a trigger and the Al-Muayyad urban santri is positioned as an active subject subject with a myriad of potential socioeconomic knowledge and experience. With the inclusion of entrepreneurial influence in urban pesantren such as al-Muayyad, students can be directly involved through the use of social digital media in marketing and introducing local products and potentials around the pesantren or their place of origin. It is hoped that pesantren can advance the Indonesian state towards the 2015 ASEAN Community by the people and for the people digitally through the active participation of the Ministry of Communication and Information and the Ministry of Tourism and Culture of the Republic of Indonesia as a catalyst.